2008
DOI: 10.1080/17486020701742608
|View full text |Cite
|
Sign up to set email alerts
|

Undrained behaviour of Changi sand in triaxial and plane-strain compression

Abstract: The results of an experimental study of the undrained behaviour of Changi sand under axisymmetric and plane-strain conditions are presented. K 0 consolidated undrained plane-strain tests and K 0 or isotropically consolidated triaxial tests on very loose and medium dense specimens were conducted. The undrained behaviour of sand at very loose and medium dense states under plane-strain conditions was characterised and compared with that under axisymmetric conditions. It was observed that the undrained behaviour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
(46 reference statements)
5
4
0
Order By: Relevance
“…The failure envelope was also compared between different type of tests with principal stress rotation, e,g., in CK 0 UC, CK 0 UE and CK 0 UDSS tests (see Figure 5.38). It is observed that the CK 0 UPS test gives the highest failure envelope, which is consistent with previous studies, such as Ladd & Lambe (1963), Ladd et al, (1980), Wanatowski & Chu (2008) and Mayne et al (2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The failure envelope was also compared between different type of tests with principal stress rotation, e,g., in CK 0 UC, CK 0 UE and CK 0 UDSS tests (see Figure 5.38). It is observed that the CK 0 UPS test gives the highest failure envelope, which is consistent with previous studies, such as Ladd & Lambe (1963), Ladd et al, (1980), Wanatowski & Chu (2008) and Mayne et al (2009).…”
Section: Discussionsupporting
confidence: 92%
“…As seen from Figure 5.38, the CK 0 UPS tests gave the highest failure envelope, i.e., CK 0 UPS tests gave the highest undrained shear strength (c u ) at the same stress level. This is consistent with many other previous studies (Ladd & Lambe, 1963;Ladd et al, 1980;Wanatowski & Chu, 2008;Mayne et al, 2009).…”
Section: Comparisonsupporting
confidence: 94%
See 1 more Smart Citation
“…This was proved, e.g., by the results of experiments carried out on Todi Clay, presented in the above mentioned work of Burland [7]. As far as the influence of boundary conditions on the shape of failure surface and parameters describing it is considered, Jefferies and Shuttle [36] and Wanatowski and Chu [79,80] in their studies of noncohesive soils proved that the aforementioned parameter M takes smaller values in plain strain compression than in triaxial conditions. This means that M value is affected by the intermediate principal stress.…”
Section: Variability Of Parameters In the Light Of Current Researchmentioning
confidence: 81%
“…Wanatowski and Chu's [30] investigation on the undrained behaviour of Changi sand shows a continuous Advances in Civil Engineering strain-hardening behaviour for the medium-dense sand, which results in effective stress path approaching a constant stress ratio (asymptotic behaviour). Similar behaviour is also reported by other researchers and in different conditions [31][32][33][34].…”
Section: Validation Results and Discussionmentioning
confidence: 99%